An Ode to Usungan - Mohamad Faizuan, Mat (2025)
An Ode to Usungan draws upon the rich heritage of Malay coastal culture, where the usungan—a ceremonial carriage—embodies both spiritual and communal significance. Infused with the essence of Iqra (the call to read and seek knowledge) and the fluid elegance of Jawi script, the work reinterprets this traditional form as a vessel carrying the wisdom, faith, and resilience of maritime Malay communities. Through symbolic composition and layered meaning, the usungan becomes a metaphor for the intellectual and cultural journeys that transcend shorelines. Exhibited in Ise to Ise: A Reflection of BIMP-EAGA Brunei Indonesia Malaysia Philippines Art Exhibitions—a prestigious international platform showcasing the finest cross-cultural expressions in the region—this piece honours the past while engaging in a contemporary dialogue about identity, knowledge, and continuity.